Governance, tourism and inclusive growth in Africa - Toyo Amegnonna Marcel Dossou; Simplice Asongu; Emmanuelle Ndomandji Kambaye; Kouessi P. Dossou; Alastaire Sèna Alinsato (African Governance and Development Institute (AGDI), 2023)
The use of GDP per capita as a measure of economic growth has been recently subject to a wide criticism by many economists. It has been observed that while some countries have experienced economic growth in recent years, income inequality and poverty continue to be exacerbated. Recently, SDG 8 has been geared to promote inclusive growth. Considering this fact, this study expands the literature by examining the relationship between tourism development and inclusive growth for a panel of 44 African countries over the period 2000-2020. Further, the study also adds to the literature by examining the moderation of governance quality on the tourism-inclusive growth nexus. The investigation is made using the GMM as an estimation technique. The result indicates that tourism and governance quality appear to promote inclusive growth. Moreover, the results indicate that good quality of institutions or governance could complement tourism development to promote inclusive growth, as positive synergies are apparent from the role of governance in moderating the incidence of tourism on inclusive growth. Policy implications are discussed.
Keywords: 330; Governance; tourism; inclusive growth; Africa